IDENTITY CONSCIOUSNESS IN CHIMAMANDA NGOZI ADICHIE’S AMERICANAH (International Journal of Food and Nutritional Sciences, 2022)
In Americanah, Chimamanda Ngozi Adichie centers on the problems of African immigrants to America and Europe countries. Because she studied in America, Adichie, as a black woman, is familiar with racial discrimination there. She explores her personal experiences with racism and identity consciousness in America through the characters in this novel. Americanah is a term used in Nigerian dialect to describe people who have lived in the United States and acquired American mannerisms. The book Americanah tells the story of the protagonist, Ifemelu. Ifemelu first meets Obinze in secondary school, and she instantly falls in love with him. Ifemelu immigrates to the United States to pursue her college education. The story is primarily narrated from Ifemelu's perspective. The narration changes to Obinze's point of view for some of the story to describe the struggles he encountered as an illegal worker in London and his quick rise to wealth upon returning to Nigeria. When Ifemelu immigrates to America, she loses her sense of identity. She had to consider being black in America, but she never had to in Nigeria.